Information and meaning in evolutionary processes - Harms, William F. (New York: Cambridge university press, 2004)
This book is intended to help transform epistemology - the traditional study of knowledge - into a rigorous discipline by removing conceptual roadblocks and developing formal tools required for a fully naturalized epistemology.
Introduction; why epistemology matters; why evolution matters; ontology, selection, and convention; Part I; Part II; Part III; preestablished harmony; 1 Replicator Theories; dawkins, replicators, and memes; Memes: The Cultural Replicators; david hull: replicators and the evolution of science; Science as a Selection Process; dennett's intentional-informational replicators; What Exactly Is a Meme?; conclusion; 2 Ontologies of Evolution and Cultural Transmission; an ontology of the cell; horizontal transmission; cultural transmission as a cellular process. Memetics: the ''meme's-eye view"three kinds of selfishness in evolution; lineages and populations; conclusion; 3 Population Dynamics; simple selection; modeling evolution; population models; mutation; frequency-dependent fitness; selection-mutation in fixed-size populations; sampling error or drift; conclusion; 4 Information Theory; information basics; why entropy? what metaphysics?; dretske's indicator semantics; using functions to determine informationally relevant states; a tracking efficiency measure for naturalized epistemology; information and payoffs. Pareto optimization of adapted responsesconclusion: four concepts of information; 5 Selection as an Information-Transfer Process; putting it all together; states of the world and the population; the proof; other receiver characterizations; the slogan; 6 Multilevel Information Transfer; information and selection on two levels; human knowledge; common sense; objections; 7 Information in Internal States; the model: real's bumblebees; preference formation: adding a third level; variable environments; simulation results; Information and Selection; 8 Primitive Content; meaning conventions
Includes bibliographical references and index.
Keywords: Knowledge, Theory of; Evolution